2014
DOI: 10.1111/jgh.12333
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for patients with unresectable advanced hepatocellular carcinoma with invasion to intrahepatic large vessels: Efficacy and outcomes

Abstract: RT is an effective treatment option without serious adverse events. RT should be considered for the patients with better hepatic function who have invasion to IHLVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Tanaka et al suggested that RT was an effective treatment without serious adverse events for patients with HCC involving invasion to intrahepatic large vessels [26]. A previous study showed that the mOS was only 13.1 months for 2D-RT alone [27].…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al suggested that RT was an effective treatment without serious adverse events for patients with HCC involving invasion to intrahepatic large vessels [26]. A previous study showed that the mOS was only 13.1 months for 2D-RT alone [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent PS analysis of sorafenib alone versus sorafenib combined with TACE for advanced HCC (in which 20-30% of the patient population had major trunk PVTT), neither regimen produced a significant benefit in OS [24]. We previously reported that RT produced favorable survival benefits without the hardships associated with conventional treatment for macroscopic hepatic vascular invasion [8,17]. …”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for patients who received RT were as follows: (i) unresectable HCC with macroscopic hepatic vascular invasion; (ii) C-P class A or B hepatic function; (iii) an ECOG performance status of 0–2; (iv) no refractory ascites; and (v) no previous radiation therapy of the liver. The RT procedure was performed as described previously [8,17]. Briefly, macroscopic hepatic vascular invasion was mainly irradiated, regardless of the presence or absence of multinodular HCC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These technologies can deliver maximal radiation doses to hepatic tumors without causing serious complications 15,16. Several studies have shown good local tumor control and long-term survival in HCC patients with PVTT treated using 3DCRT 1721…”
Section: Introductionmentioning
confidence: 99%